Assessing field-scale salt leaching during saline soil remediation with electrical resistivity tomography and electromagnetic induction methods - You, Yanhui; Fu, Wei; Liu, Haixia; Li, Guoqing; Wang, Shiqin; Pan, Xicai; Wang, Xinbin; Yang, Jinle; Wang, Chaowei (Frontiers in Environmental Science, 2025)
During the remediation of saline wasteland, it is crucial to rapidly and accurately characterize the spatial distribution and temporal dynamics of soil salinity for evaluating the efficacy of leaching measures and guiding management strategies. In this study, electrical resistivity tomography (ERT) and electromagnetic induction (EMI) were deployed in a saline wasteland in the Jingtai Yellow River Irrigation District, Gansu Province, China, to monitor field-scale changes in salinity before and after salt leaching. A calibrated model linking soil bulk electrical conductivity and ground temperature to total dissolved solids (TDS) was applied to convert geophysical results into quantitative TDS values, enabling quantitative assessment of field-scale salt removal rates. Monitoring indicated that salinization was mainly caused by a rising groundwater table resulting from inadequate drainage, which led to evaporation-driven salt accumulation in low-lying areas and eventual land abandonment. Although remediation measures—including dredging drainage ditches and conducting salt-leaching irrigation—were implemented, their effectiveness was spatially heterogeneous due to the presence of low-permeability layers such as clay pans or caliche. For instance, along a transect 5 m from a newly dredged ditch, the desalination rate reached 87.8% after one leaching event. In contrast, along a transect 85 m from the ditch, the rate was only 16.8% after dredging and leaching. These findings underscore the need for targeted salt control strategies and optimized winter irrigation protocols to improve regional salinity management.